Researching motivation and emotion of Chinese older adults in English language learning - Geng, Yanchuan (2021)
In China, there has been a dramatic increase in the number of older adults who are engaged in learning English as a second/foreign language (hereafter L2) in their post-retirement life, aiming to accrue presumed physical, social and psychological benefits. However, although reasons for older adults to participate in learning activities in general have been extensively researched, such research rarely focusses on an L2 and related emotional aspects. This study investigates the L2 motivation of Chinese older adults and the relationships between their motivation and emotion. Research on this theme is urgently needed. There is limited research in the field of adult learning in education that focuses on the particularities behind the choice of learning English as a subject or set of skills or which discusses how the learning motivation might change dynamically in the process. This shortage of studies might, admittedly, be addressed within the rapidly expanding field of L2 motivation studies, but only in a partial manner. This is because the findings of L2 motivation studies are predominantly based on younger learners rather than on retired older adults who may display distinctive learning features. Further, the links between L2 motivation and a fuller spectrum of emotions have only recently attracted attention from scholars, and these links merit further investigation.